Profil Tuberkulosis Pada Anak di Instalasi Rawat Jalan RSUD. Raden Mattaher Jambi - Irawan Anasta Putra; Amelia . (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2013)
ABSTRACT Background: Tuberculosis (TB) in children is a very worrying phenomenon because it potentially causes a variety of problems, starting from cases of failure to growth, disability and even death. The symptoms of Tuberculosis in children are often non specific, so that,  over diagnosis  and followed by over treatment are often happen. In another cases, under diagnosis and under treatment are also found. TB diagnosis in children refers on finding the mycobacterium (MTB) from sputum, gastric lavage, biopsy, etc.  But, these kind of examinations are difficult and rare to get and it makes almost of tuberculosis diagnosis in children enforced by clinical symptoms,  radiological imaging and tuberculin test. Objective: The aim of this research is to know the profile of patients with tuberculosis in children in outpatient installation of Raden Mattaher Hospital Jambi. Methods: Descriptive-prospective research. The subject of this research is all children who gets treatment in outpatient policlinic of pediatrics and already diagnosed as TB (New case) by pediatrician which based on criteria and scoring system from IDAI. Results: Tuberculosis in boys (60%), comparing with girls 3 : 2. Age group under 5 years (56%) and primary school age (44%). Children with poor nutrition and malnutrition (60%). Children with BCG immunization and positive scar (60%), and children with BCG Immunization and negative scar (43%). The most presenting symptoms and signs were cough (96%), fever (84%), history contact of adult with tuberculosis (60%), positive Tuberculin Test (42%) and Radiographic findings of Tuberculosis (78%) Conclusion: The most common patients was in age group under 6 years (56%) and 6-12 years (42%). The most important high risk of tuberculosis infection in children is contact of adult with tuberculosis. Therefore, it is important to detect infection of tuberculosis in adult and find out its transmission in order to early detecting of child with high risk of tuberculosis infection. Prevention of tuberculosis in children is one of the most important thing to do. Keyword: Tuberculosis in children. Contact of adult with tuberculosis. Clinical symptoms and Tuberculin Test.